PERLINDUNGAN HUKUM TERHADAP PEKERJA DALAM PERJANJIAN KERJA WAKTU TERTENTU BERDASARKAN UNDANG-UNDANG NOMOR 13 TAHUN 2003 TENTANG KETENAGAKERJAAN (STUDI DINAS KETENAGAKERJAAN KOTA MAKASSAR) - Hafid, Muhammad Irvan (Al-Hikmah, 2019)
The study was conducted and aims to: 1) To find out the Legal Protection of Workers in a Specific Time Work Agreement Based on Law Number 13 of 2003 concerning Manpower in the Legal Area of the City of Manpower of Makassar City; 2) To find out and analyze what factors are hampering the legal protection of workers in the Certain Time Work Agreement for the Legal Area of the City of Manpower Makassar. This type of research is empirical legal research that is legal research that examines the implementation or implementation of positive legal provisions (legislation) factually in any particular legal event that occurs in society. The legal material used consists of primary legal data and secondary legal data. Legal data collection techniques are collected through literature studies and field studies. Then the techniques to analyze with qualitative analysis techniques by sorting and selecting, classifying, and linking the realities that occur in the field with the problems studied, so as to provide a clear picture of what is happening in the field so that it comes to a conclusion. The results showed that: 1) Legal Protection of Workers in a Specific Time Work Agreement Based on Law Number 13 Year 2003 Regarding Employment in the Legal Area of the City of Makassar Employment Service is still not optimal, it can be seen from the number of cases of layoffs due to temporary employment contract in the contents of the work agreement are not explained about the type of work and the time of work even though the status of the worker / laborer is PKWT; 2) The inhibiting factors in the legal protection of workers in certain time work agreements are the legal areas of the Makassar City employment department that are related to regulations, in addition there are also constraints related to the making / or form of a specific time work agreement (PKWT), finally the constraints supervision.